Ki Hajar Dewantara: Pendidikan Agama Islam Sebagai Proses Transformasi Sosial - Fachri Sugiharto; Qoim Nurani (Nusantara: Jurnal Pendidikan Indonesia, 2022)
The background of this research is concerned with the phenomenon of social transformation that occurs in Indonesia. The social transformation offered by the current globalization requires changes in various aspects, both economic, political, socio-cultural, and moral, including aspects of education. The purpose of this study was to examine the relevance of Ki Hajar Dewantara's Islamic education thought as a process of social transformation in the current era. The method used is library research. Data collection is done by the documentation method. The method used is a descriptive-analytic method. The results of the study show that: 1) Islamic education is the first level of teaching, which teaches the existence of eternal life afterlife in the world. 2) Education as a process of social transformation must pay attention to every element in education. The family is the smallest element that must set a good example, namely etiquette, and character. Goals must be adapted to the conditions, circumstances, and needs of the community. The school environment must teach intellectual intelligence and other education to equip students to become someone who can bring change for the better.